Labour Policy For Overcoming The Impact of Covid-19 - Sulistyani Eka Lestari (Faculty of Law, Merdeka University Surabaya, 2021)
During the Covid-19 epidemic pandemic, the government has done a lot of policies, in order to overcome the widespread corona virus outbreak and reduce the number of victims. In dealing with the Covid-19 outbreak, the government issued several policies, one of which was the Circular of the Minister of Manpower Number M / 3 / HK.04 / III / 2020 regarding guidelines for Labor Protection and Business Continuity in Prevention and Subscription Coordination. However, this Circular Letter is deemed insufficient to solve labor problems during the Covid-19 pandemic.The Minister of Manpower circular is deemed inappropriate if the government regulates the labor sector in dealing with Covid-19 only through the Minister of Manpower's Circular Letter. The government should issue better policies such as Ministerial Regulations or higher so that they have the authority and binding force. Government policies on employment must be able to provide guidance and clarity for industrial relations actors in facing the current Covid-19 pandemic.